Use of mining and metallurgical waste as a backfill of worked-out spaces - Bolatova, A.; Kuttybayev, A.; Kаinazarov, А.; Hryhoriev, Yu. I.; Lutsenko, S. A.; Григор’єв, Ю. І. (THE NATIONAL ACADEMY OF SCIENCES OF THE REPUBLIC OF KAZAKHSTAN, 2022)
The sustainable growth of the economic development of the mining industry directly depends on the level of implementation of innovative technologies in production. Rational use of subsoil in the development of deposits should be based on the maximum completeness and complexity of extraction of useful components. Today, the issue of introducing low-waste and non-waste environmentally friendly technologies is especially acute. The main direction of using waste from mining and metallurgical production is the filling of mined spaces. There is extensive experience in the use of production wastes in stowing operations, technologies for stowing operations have been developed, which are used in many mines at the mines of East Kazakhstan. One of the urgent tasks in these conditions is the development of resourcesaving technologies for the extraction of minerals based on the diversification of the products of mining enterprises, which ultimately will reduce the cost of mining and increase the profitability of production and the competitiveness of the final products of mining companies. The article provides a substantiation of the main direction of using mining and metallurgical waste as a backfill of mined spaces, a resource-saving technology of mining based on the diversification of the output of mining enterprises, parameters of reducing the cost of mining and increasing the profitability of production and the competitiveness of the final products of mining companies and parameters of reliable artificial massifs in mining systems with backfilling of mined spaces are given [1]. It is recommended to use the technology at mining enterprises with complex mining and geological conditions.
Keywords: underground method; filling operations; safety factor; mining; mixture